2020
DOI: 10.3390/s20051538
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Geiger–Müller and Cadmium Zinc Telluride Sensors Envisaging Airborne Radiological Monitoring in NORM Sites

Abstract: Radiological monitoring is fundamental for compliance with radiological protection policies in the aftermath of radiological events, such as nuclear accidents, terrorism, and out-of-commission uranium mines. An effective strategy for radiation monitoring is to use radiation detectors coupled with Unmanned Aerial Vehicles (UAVs), enabling for quicker surveillance of large areas without involving the need of human presence in the target area. The main aim of this study was to formulate the parameters for a UAV f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Upon landing, it starts measuring and recording CZT readings from the ground for as long as the operator decides for. In our previous work [20], we found that 30 minutes provides enough time to retrieve the signature of the radionuclides present on the ground.…”
Section: Inspection Flightmentioning
confidence: 95%
See 2 more Smart Citations
“…Upon landing, it starts measuring and recording CZT readings from the ground for as long as the operator decides for. In our previous work [20], we found that 30 minutes provides enough time to retrieve the signature of the radionuclides present on the ground.…”
Section: Inspection Flightmentioning
confidence: 95%
“…Furthermore, radiological sensors such as the GMC need to be close to its sources to be able to detect relevant data. This sensor, performance and limitations have been described in the previous paper of the project [20]. According to our previous work, the sensors need to be at a maximum range of 1m from the ground, the drone should fly at a speed of ≈ 0.2m/s and height of 1m.…”
Section: Flightmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that these detection systems are normally based on consumer-generated sensing (can be operated by citizens), sensor networking (by integrating collaborative missions to create a big picture), are lightweight and low cost equipment, makes them important tools to be used, for example, in the aftermath of a nuclear accident or to assess the effectiveness of decontamination efforts. MARIA project reported some constraints related to the survey speed and the distance detector-source is not constant and changes with user, and the difficulty in estimating only with the mobile phone and GPS) [ 140 , 141 ]. POKEGA project referred some limitations: the smartphone has an extremely low input gain and slow sampling rate (output signal from PIN photodiode is low and narrow), noise vibration susceptibility (incorrect readings), the energy consumption (smartphone battery insufficient), and the limited measuring range (sampling limitations) [ 138 ].…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…For high resolution mapping at NORM sites, particularly decommissioned uranium mines, a lightweight gamma spectrometer coupled to a multi-rotor was proposed [ 140 , 158 ]. While Martin et al [ 158 ] proposed a CZT to scan the area at 5–15 m AGL and speed 1.5 m/s, Borbinha et al [ 140 ] suggested lower altitudes and speeds (1–2 m height and 0.2–0.23 m/s) using a GM for a first monitoring (hotspot identification) and only after the use of a CZT for hotspot inspection (energy spectra obtained at 10–20 cm from the ground—platform landed). The latter is related to the FRIENDS project, which consists of using a combination of sensors coupled in a fleet of drones (autonomous and cooperative navigation) with the goal of monitoring and mapping in real time areas with high concentrations of NORMs.…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%